Interprofessional Skills Learning Guide: A Multimedia E-Book for Small-Group or Individual Learning - Heather Ward; Sharon Elizabeth Card; Dylan Chipperfield; Suzanned M. Sheppard; Franke Bulk; Wayne Giesbrecht (Association of American Medical Colleges, 2016)
Abstract Introduction Redefining learning space beyond physical classrooms with fixed resources is necessary to address challenges of interprofessional learning in a clinical setting. This multimedia e-book introduces recognized team skills of shared mental models, situational awareness, and the SBAR (situation, background, assessment, and recommendation) communication tool for individual or small-group learning. The e-book was derived from work done to develop an interprofessional small-group interactive learning tool for use in a clinical environment where resources, including meeting space, time, and facilitators, were limited. It is designed for individuals early in their clinical training but who have had previous clinical experience. Methods Utilizing readings, a series of videos, and reflective questions, a virtual narrator guides learners through an interactive case regarding a virtual chronic obstructive pulmonary disease patient preparing for discharge. Results Thirty-two responders evaluated the learning content as being clinically relevant. Comments encouraged all health care providers to become familiar with these interprofessional tools. Discussion Electronic, human, and space resources are often limited, especially in the clinical/education interface of the hospital or clinic environment for embedded interprofessional learning opportunities. The multimedia e-book provides a stand-alone learning resource for individuals or small groups of the same or different professions, with the opportunity for interactive learning with minimal space and human resource requirements.